Hasanchelebi: A Killing Station for Armenian Men on the Sebastia Deportation Routes - Sukiasyan, Robert (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
This article investigates Hasanchelebi, a key station on the Sebastia deportation routes, as the principal site for the systematic extermination of deported Armenian men from Sebastia and surrounding regions during the Armenian Genocide. Drawing on Armenian survivor testimonies and corroborating Ottoman documents, the study reconstructs the phases of atrocities, beginning with the plunder and abuse of women and culminating in the mass arrest and execution of men. It highlights the strategic role of Hasanchelebi in the genocidal machinery and demonstrates the unique opportunities provided by Armenian sources for documenting and understanding the Armenian Genocide.
Keywords: Ottoman Empire; Armenian Genocide